2013
DOI: 10.18662/rrem/2013.0501.08
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Some Simple Strategies to Enhance Learners’ Listening Skills

Abstract: This action research was carried out with an intermediate EFL class of 37 students (19 women and 18 men) at a prestigious public university of a major city in Ecuador. After I gave them the first quiz, I noticed that most of the class performed very poorly on the listening part. I decided to find out what the problem was and what I could do to help my students to improve their listening skills. When I asked the class why they thought they did badly on the listening they came up with different reasons: "The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…We tried to avoid difficulties while listening, taking into consideration data from the research of N. Vyspinska, so we paid special attention to such factors that affect students achievements in listening as: rate of delivery, new vocabulary, length of listening, visual support and background noise (2019, p.302). We also implemented strategies to improve listening skills (Caro, 2013). After listening, we parsed the text in graphical form to identify its features: unfamiliar vocabulary and grammatical structures.…”
Section: Methodsmentioning
confidence: 99%
“…We tried to avoid difficulties while listening, taking into consideration data from the research of N. Vyspinska, so we paid special attention to such factors that affect students achievements in listening as: rate of delivery, new vocabulary, length of listening, visual support and background noise (2019, p.302). We also implemented strategies to improve listening skills (Caro, 2013). After listening, we parsed the text in graphical form to identify its features: unfamiliar vocabulary and grammatical structures.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous scholarly inquiries have been conducted to examine the influence of listening techniques on students' listening subskills, as evidenced by the works of Caro (2013), andZare-Behtashet et al (2017). However, it is important to acknowledge that the data collection methods employed in these investigations encompassed tests and questionnaires.…”
Section: Related Studiesmentioning
confidence: 99%
“…An action research was carried out with an intermediate EFL class of 37 students at a public university in Ecuador by CARO (2013). Realizing that the students performed very poorly on the listening tests, the author decided to implement some simple strategies namely listening for gist, listening for details, and reading the questions carefully before the listening task, alongside a number of metacognitive strategies.…”
Section: Findings Of Previous Studiesmentioning
confidence: 99%
“…Second, results showed that the students in studies were more aware of the usefulness of listening strategies. They perceived listening improvement in academic listening and real world listening situations; raising strategy awareness, increasing confidence in English listening abilities (Khaled, 2012;Yi Guan, 2014;CARO, 2013;Abdullah, 2010;Le Thi Hang, 2006). After strategy instruction course, the students are found to use more listening strategies than before the course (Nantikarn, 2016;Vandergrift, 2003).…”
Section: Commonalities Of Previous Studiesmentioning
confidence: 99%